2017
DOI: 10.1002/pds.4278
|View full text |Cite
|
Sign up to set email alerts
|

National trends in long‐term use of prescription opioids

Abstract: The findings highlight the need for research on potential benefits and harms of long-term use of opioids and efforts to restrict long-term use to patients for whom the benefits outweigh the risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 36 publications
2
71
1
Order By: Relevance
“…From 1999 to 2010, there has been a significant increase in the use of medications that act through or have effects on serotonin receptors and levels including a large list of anti-depressant medications including monoamine oxidase inhibitor (MAOI) or selective serotonin reuptake inhibitor (SSRI) [19]. This has led to an increased incidence of serotonin syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…From 1999 to 2010, there has been a significant increase in the use of medications that act through or have effects on serotonin receptors and levels including a large list of anti-depressant medications including monoamine oxidase inhibitor (MAOI) or selective serotonin reuptake inhibitor (SSRI) [19]. This has led to an increased incidence of serotonin syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…LTOT can lead to tolerance and escalating doses, and is associated with greater risk of opioid‐related overdose and mortality . Across populations and health care settings, the rising prevalence of LTOT has paralleled increases with opioid‐related overdose and mortality rates . Previous studies, which defined LTOT as opioid use of more than 90 days, found that the prevalence of LTOT was 5.4% in the United States and 17% in Canada …”
Section: Introductionmentioning
confidence: 99%
“…6 Across populations and health care settings, the rising prevalence of LTOT has paralleled increases with opioid-related overdose and mortality rates. [7][8][9][10][11][12][13] Previous studies, which defined LTOT as opioid use of more than 90 days, found that the prevalence of LTOT was 5.4% in the United States and 17% in Canada. 11,14 Defining LTOT is critical to understanding the risk factors that lead to LTOT and the evaluation of clinical practices and policies aimed at reducing risky opioid use that may occur with LTOT (eg, high doses, concurrent benzodiazepine prescriptions, or other forms of opioid use that are associated with behaviors related to abuse, misuse, and addiction).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies discuss the rising opioid use in the United States and Europe focusing on different settings including primary care and nursing homes …”
Section: Discussionmentioning
confidence: 99%